ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI PROVINSI JAWA TENGAH PERIODE 2010-2014 - Hapsari, Adinda Putri; Iskandar, Deden Dinar (Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
This study aims to analyze the influence of capital expenditure, private investment, population, education on economic growth in the province of Central Java 2010-2014 years. The method of analysis used is panel data regression with fixed effect approach. The result of regression analysis shows that variable of capital expenditure, population, and education have a significant positive effect to economic growth. Private investment variable has negative and insignificant effect on economic growth, while health variable has significant negative effect to economic growth.